2018
DOI: 10.1108/ijsms-01-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Investigating social media consumption, sports enthusiasm, and gender on sponsorship outcomes in the context of Rio Olympics

Abstract: Purpose Using the context of Rio Olympic games, the purpose of this paper is to investigate attitude toward sponsorship outcome as it relates to purchase behavior, gender, sponsor patronage, sports enthusiasm, and social media consumption. Design/methodology/approach Data were collected using an online survey of 265 participants. Questions regarding demographics, viewing habits, sports participation, enthusiasm, attitude toward Olympic events were included in the survey. The four sub-scales were sponsorship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
14
0
5
Order By: Relevance
“…However, there is no consensus in the literature regarding the effects of gender and age on different variables linked to sporting activity (e.g. Conaway and Cort es-Garay, 2014;Greenwell et al, 2015;Hazari, 2018;Janssen et al, 2017;Molanorouzi et al, 2015;Zurita-Ortega et al, 2018).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus in the literature regarding the effects of gender and age on different variables linked to sporting activity (e.g. Conaway and Cort es-Garay, 2014;Greenwell et al, 2015;Hazari, 2018;Janssen et al, 2017;Molanorouzi et al, 2015;Zurita-Ortega et al, 2018).…”
Section: 3mentioning
confidence: 99%
“…The effectiveness of gamification as a mechanism to achieve perceptions of greater selfefficacy may be influenced by the characteristics of the users themselves, such as the sociodemographic variables of gender and age (Conaway and Cort es-Garay, 2014;Haro-Gonz alez et al, 2018;Hazari, 2018;Janssen et al, 2017;Song et al, 2018). In the sports context, it has been observed that women are less active than men and that older people are less active than younger people (European Commission, 2018;Spanish Ministry of Education, Culture and Sport, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Social media research in sport management has mainly examined fan behavior, such as fan engagement on social media (Osokin, 2019; Santos et al , 2019) or general usage behavior with regard to electronic word of mouth (Wakefield and Bennett, 2018; Chang, 2019; Kim and Kim, 2020). Further research examined the fan and usage behavior of large public groups on social media during mega events such as the Olympic Games (Finlay, 2018a, b; Hazari, 2018; Li et al , 2018; Tang and Cooper, 2018; Yoon and Pedersen, 2018) or the UEFA Champions League Final (Yan et al , 2019). Another stream of research analyzed sport consumers' interests in social media and identified motives for social media consumption (Li et al , 2019; Spinda and Puckette, 2018; Tu et al , 2019; Watanabe et al , 2019).…”
Section: Literature Review: Digital Transformation In Sport Management Researchmentioning
confidence: 99%
“…This behavioral view is aligned with one of the main aspects of the relationship between sports clubs and their public, which is the level of engagement grounded in the practices of buying tickets, attending games at stadiums, and commenting on social media posts (Florea et al , 2018). Hence, due to the popularity of social media and its relevance to marketing and branding efforts (Jin et al , 2019), investing in driving that type of engagement via branded content could maintain and nurture a two-way communication with fans (Abeza et al , 2019), improve data collection (Moussa, 2019), attract sponsorship (Hazari, 2018) and increase brand awareness (Aichner, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%